Dual fluorescent hollow silica nanofibers for in situ pH monitoring using an optical fiber. Issue 8 (15th February 2023) - Zhou, Junhu; Ren, Yundong; Nie, Yuan; Jin, Congran; Park, Jiyoon; Zhang, John X. J.
Abstract : This study reports a sensitive and robust pH sensor based on dual fluorescent doped hollow silica nanofibers (hSNFs) for in situ and real-time pH monitoring. Abstract : This study reports a sensitive and robust pH sensor based on dual fluorescent doped hollow silica nanofibers (hSNFs) for in situ and real-time pH monitoring. Fluorescein isothiocyanate (FITC) and tris(2, 2′-bipyridyl)dichlororuthenium(ii ) hexahydrate (Ru(BPY)3 ) were chosen as a pH sensitive dye and reference dye, respectively. hSNFs were synthesized using a two-step method in a reverse micelle system and were shown to have an average length of 6.20 μm and average diameter of 410 nm. The peak intensity ratio of FITC/Ru(BPY)3 was used to calibrate to solution pH changes. An optical-fiber-based fluorescence detection system was developed that enabled feasible and highly efficient near-field fluorescence detection. The developed system enables fully automated fluorescence detection, where components including the light source, detector, and data acquisition unit are all controlled by a computer. The results show that the developed pH sensor works in a linear range of pH 4.0–9.0 with a fast response time of less than 10 s and minimal sample volume of 50 μL, and can be stored under dark conditions for one month without failure. In addition, the as-prepared hSNF-based pH sensors also have excellent long-term durability. Experimental results from ratiometric sensing confirm the high feasibility, accuracy, stability and simplicity of the dual fluorescent hSNF sensors for the detection of pH in real samples.